Quercetin Regulates Calcium and Phosphorus Metabolism Through the Wnt Signaling Pathway in Broilers - Wang, Bo; Wang, Shanshan; Ding, Manyi; Lu, Han; Wu, Hao; Li, Yao (Frontiers in Veterinary Science, 2022)
This study intended to explore the effect and mechanism of different doses of dietary quercetin on calcium and phosphorus metabolism to provide an experimental basis for preventing leg disease in broilers. A total of 480 1-day-old healthy Arbor Acre broilers were randomly allotted into four groups (0, 0.02, 0.04, 0.06%) for 42 days. Compared with control, 0.06% quercetin significantly increased the unit weight and the relative weight of tibia in broilers (P < 0.05). Meanwhile, phosphorus content and bone mineral density (BMD) were significantly increased by 0.06% dietary quercetin supplementation in tibia (P < 0.05). Ash of tibia was significantly increased by 0.04 and 0.06% quercetin in broilers (P < 0.05). In addition, 0.06% quercetin significantly increased the content of serum calcium-binding protein (CB), estradiol (E2), osteocalcin (OC), alkaline phosphatase (ALP), and calcitonin (CT) (P < 0.05); 0.04% quercetin significantly increased 1,25-dihydroxyvitamin D3 (1,25-(OH)2D3) (P < 0.05) content in serum of broilers. The content of serum parathyroid (PTH) was significantly decreased by 0.02 and 0.06% quercetin (P < 0.05) in broilers. Gene Ontology (GO) functional annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that the Wnt signaling pathway was a key signaling pathway of calcium and phosphorus metabolism in broilers which was significantly regulated by quercetin. The differentially expressed genes (DEGs) from transcriptome sequencing were validated with real-time quantitative PCR (RT-qPCR). In conclusion, 0.06% dietary quercetin supplementation improved calcium and phosphorus metabolism by regulating the Wnt signaling pathway in broilers.